2017
DOI: 10.1111/jcpp.12720
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Critical considerations for studying low‐functioning autism

Abstract: Jack and Pelphrey provide a systematic review of neuroimaging studies in understudied populations within the autistic spectrum, focussing specifically on those with minimal verbal ability, intellectual disability and developmental regression. Despite accounting for nearly a third of the autistic spectrum, the number of studies focussing on these populations is extremely low. This review highlights a critical need for further neuroimaging research on these populations, and provides practical suggestions for ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…It could be argued that individuals “coping better” are more likely to volunteer to speak about their experience, and so we may not gain an accurate perspective for the full spectrum. Individuals on the autism spectrum with intellectual disability and/or minimal language are generally neglected in research and it is important to consider how their views can be gathered and how they can be brought into participatory research models (Chakrabarti 2017 ).…”
Section: Study Limitationsmentioning
confidence: 99%
“…It could be argued that individuals “coping better” are more likely to volunteer to speak about their experience, and so we may not gain an accurate perspective for the full spectrum. Individuals on the autism spectrum with intellectual disability and/or minimal language are generally neglected in research and it is important to consider how their views can be gathered and how they can be brought into participatory research models (Chakrabarti 2017 ).…”
Section: Study Limitationsmentioning
confidence: 99%
“…There has been an explosion of research in the field of autism, as evidenced by a 24-fold increase in the number of papers published on the topic over the past three decades (Chakrabarti 2017 ). Despite this proliferation, many experts have noted that those severely affected by autism spectrum disorder (ASD) appear to have been understudied.…”
Section: Introductionmentioning
confidence: 99%
“…The current study does not answer this question, since there is no control condition with nonsocial stimuli. However, in a previous study, we have shown that the impact of autistic traits on reward modulation of automatic mimicry was seen for social but not nonsocial stimuli (68). Future studies should explicitly test this possibility using the current paradigm.…”
Section: Discussionmentioning
confidence: 76%